The Influence Of Linkages And Information Sharing On Supply Chain And Export Performance At Pt. Bintang Samudera Angkasa Company - Luthfi Albern Liharto; Ratih Hendayani (Telkom University, 2025)
Exports and imports are crucial elements in a country's economy, including Indonesia, as they play a significant role in driving economic growth and societal welfare. In recent years, Indonesia has faced challenges in international trade, such as fluctuations in global commodity prices and increasing competition. Therefore, it is essential for companies to enhance their export performance by focusing on high-value-added products and supply chain efficiency. This study aims to evaluate the impact of linkages and information sharing on supply chain and export performance at PT. Bintang Samudera Angkasa, a logistics company involved in global shipping. Strong linkages among supply chain entities and accurate information sharing are expected to improve operational efficiency and product competitiveness in international markets. Using a quantitative method, this study involved 80 respondents from employees and managers at PT. Bintang Samudera Angkasa, with data analyzed through the SMARTPLS software. The results of the study indicate a positive and significant relationship between supply chain linkages and information sharing on the supply chain and export performance of the company. These findings highlight the importance of strengthening relationships among stakeholders within the supply chain and effectively utilizing information for operational efficiency. This study is expected to contribute to refining the business strategy of PT. Bintang Samudera Angkasa and offer valuable insights for other companies in the logistics and export sectors. It is also beneficial for academics and practitioners interested in understanding the influence of linkages and information sharing in the context of supply chain and export performance.